Implementasi Kebijakan Standar Pelayanan Minimal Pemenuhan Kebutuhan Pokok Air Minum di Kabupaten Paser - Firhansyah, Firhansyah; Maulana, Delly; Bida, Obed (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
The application of the Minimum Service Standard policy for Fulfilling Daily Drinking Water Basic Needs in Paser Regency has followed the applicable technical standards, both from the Ministry of Public Works and Public Housing, as well as from regulations issued by the Regional Government of Paser Regency itself. But actually, it is necessary to identify what are the factors that support and hinder the implementation of SPM policies. From the results of data analysis, it was found that the process of implementing the MSS policy for the drinking water sub-sector was still not under technical standards because the basic data used in calculating service needs did not refer to the local BPS Susenas data, and there was no determination of priorities and targets for implementing SPM. The supporting factors identified included: Policy standards and targets, budgetary support, organizational internal and external communications, suitability of the duties and functions of the DPUTR in Human Settlements (organizational characteristics), positive responses and support from the community, a relatively conducive political situation, full support (response) from implementers/employees, and the level of implementer tendencies were quite high and positive. Meanwhile, the inhibiting factors include the lack of number and competence of employees in the implementing organization (Cipta Karya Division of the Paser Regency DPUTR), the unstable social and economic conditions of Paser Regency, and the low level of understanding of SPM policy implementers in the drinking water sub-sector.